Do schooling reforms improve long-term health? - David Madden (IZA World of Labor, 2016)
A statistical association between more education and better health outcomes has long been observed, but in the absence of experimental data researchers have struggled to find a causal effect. Schooling reforms such as raising school leaving age, which have been enacted in many countries, can be viewed as a form of natural experiment and provide a possible method of identifying such an effect. However, the balance of evidence so far is that these reforms have had little impact on long-term health. Thus, policymakers should be cautious before anticipating a health effect when introducing reforms of this nature.
Keywords: I26; I28; I18; 330; schooling reform; long-term health; local treatment effect